Capture of In Situ Generated Diazo Compounds or Copper Carbenoids by Triphenylphosphine: Selective Synthesis of trans‐ Alkenes and Unsymmetric Azines via Reaction of Aldehydes with Ketone‐Derived N‐Tosylhydrazones. Issue 11 (9th August 2013) - Sha, Qiang; Ling, Yifei; Wang, Wenyong; Wei, Yunyang
Abstract Copper(II) acetylacetonate‐catalyzed Wittig olefination reactions of aldehydes with ketone‐derived N‐tosylhydrazones are reported. A series of tosylhydrazones was investigated and our results showed that the carbon number of the alkyl chain influences the E‐selecivity of the alkenes greatly. Alkenes could be obtained in moderate yields and excellent E‐selectivity when the carbon numbers were up to two. Under metal‐free conditions, triphenylphosphine was able to capture the in situ generated diazo compounds and the corresponding unsymmetrical azines were formed in good yields. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>